Diagnosis Infeksi Streptococcus suis serotipe-2 pada Babi Secara Serologi dengan Muramidase Released Protein (SEROLOGICALLY DIAGNOSE OF STREPTOCOCCUS SUIS SEROTYPE-2 INFECTION IN PIGS BASED ON MURAMIDASE RELEASED PROTEIN) - Salasia, Siti Isrina Oktavia; Artdita, Clara Ajeng; Slipranata, Mitra; Artanto, Sidna (Jurnal Veteriner; Vol 16 No 4 (2015), 2016)
Streptococcus suis is a bacterial pathogen causing disease of pigs that characterized by meningitis,bronchopneumonia, arthritis, pericarditis, polyserositis and septicaemia. S. suis especially serotype 2 caninfect human (zoonotic) with a special symptom of meningitis. The aim of this research was to detect S.suis infection based on muramidase released protein (MRP), as an important virulence marker of S. suis.S. suis serotype 2 strain P171 with phenotype of MRP+EF+ was used in this research. The MRP antigen wasextracted using lysozyme and separated by using sodium dodecyl sulphate-polyacrylamide gel electrophoresis(SDS-PAGE). Balb/c mice were imunized with 136 kDa MRP to produce antibody against MRP. Theantibody was evaluated by using enzyme linkage immunosorbent assay (ELISA). The results of the researchshowed that the antibody against MRP with molecular weight of 136 kDa could be produced on Balb/Cmice with the highest absorbance of 3,889 and could be used to detect field sera from infected pigs with200x dilution using ELISA antigen capture. Antibody against MRP could detect serologically of S. suisinfection in pigs in Papua with 50% seropositivy by using ELISA antigen capture and 40% by using dot blot.
Keywords: Streptococcus suis; serotype 2; muramidase released protein; antibody; zoonotic